2020
DOI: 10.1590/1519-6984.221849
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of heavy metals and its impact on DNA fragmentation in different fish species

Abstract: This study was conducted to assess water pollution by examining DNA fragmentation in selected fish organs (kidney, liver, gills, and muscle tissue) from Wallago attu, Sperata sarwari, Vulgaris vulgaris, and Labeo rohita collected from a known polluted section of the Chenab River, Pakistan, and from a control site. The fish were caught using a gill net and were assigned to three different weight groups (W1, W2, and W3) to study the degree of variation in DNA fragmentation in relation to body weight. In fish fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…These findings align with Sultana et al [ 111 ], who established a link between DNA fragmentation and heavy metal levels in various fish tissues. Moreover, Mohamed et al [ 112 ] noted that tilapia exposed to higher heavy metal levels in severely polluted areas showed a higher frequency of DNA fragmentation in the gills, liver, and muscles, potentially indicating a lack of effective DNA repair systems.…”
Section: Discussionsupporting
confidence: 92%
“…These findings align with Sultana et al [ 111 ], who established a link between DNA fragmentation and heavy metal levels in various fish tissues. Moreover, Mohamed et al [ 112 ] noted that tilapia exposed to higher heavy metal levels in severely polluted areas showed a higher frequency of DNA fragmentation in the gills, liver, and muscles, potentially indicating a lack of effective DNA repair systems.…”
Section: Discussionsupporting
confidence: 92%
“…The polyanionic nature of DNA makes it susceptible to the adherence of metal cations and the production of hydroxyl radicals that attack invariably on the nucleobases and sugar-phosphate backbone of DNA (Manoj and Padhy, 2013). The toxic properties of transition metals is due to their higher potential to act as catalysts in the production of ROS through Haber-Weiss/ Fenton reactions, resulting in potentially damaging DNA modifications (Aboul-Ela et al, 2011;Sultana et al, 2020). Fedeli et al (2010) reported increased comet parameters (tail moment, tail intensity) in the RBC's of Onchorhyncus mykiss exposed to 50 µM Cu.…”
Section: Discussionmentioning
confidence: 99%
“…In high concentrations, aluminum may provoke neurological disorders in human beings, such as Alzheimer's and Parkinson's diseases (SILVA JÚNIOR 2013). In fish, the aluminum dissolved in acidic water, which comes into contact with the gills, provokes an increase in the pH and the formation of insoluble Al 2 (OH) 3 , which damages the DNA (Muniz and Oliveira-Filho 2006;Sultana et al 2020) and eventually suffocates the animal. This has raised a number of concerns in the population of Barcarena in terms of the quality of the fish available for human consumption in the region.…”
Section: Discussionmentioning
confidence: 99%